Urbanization drives rapid convergence of riverine greenhouse gas levels in the urban agglomeration, North China - Ling Wen; Zhengkui Ge; Yulin Qi; Dietrich A. Volmer; Chao Ma; Chunmei Chen; Zhifeng Yan; Pingqing Fu; Si-Liang Li (Agriculture, Ecosystems & Environment, 2026)

Seasonal variations of nitrosamines in atmospheric PM1 in Tianjin - Yuexin Zheng; Jing Chen; Jingying Ma; Guohao Zhang; Pingqing Fu (Atmospheric Environment, 2026)

Retraction notice to “Seasonal variation and size distribution of aromatic acids in urban aerosols in Beijing, China” [Sci. Total Environ. 954 (2024) 176504] - Di Liu; Shaofeng Xu; Yunchao Lang; Shengjie Hou; Lianfang Wei; Xiaole Pan; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Science of The Total Environment, 2026)

Retraction notice to “Light absorption of black carbon and brown carbon in winter in North China Plain: comparisons between urban and rural sites” [Sci. Total Environ. 770 (2021) 144821] - Jiaxing Sun; Conghui Xie; Weiqi Xu; Chun Chen; Nan Ma; Wanyun Xu; Lu Lei; Zhijie Li; Yao He; Yanmei Qiu; Qingqing Wang; Xiaole Pan; et al. (Science of The Total Environment, 2026)

Retraction notice to “High daytime abundance of primary organic aerosols over Mt. Emei, Southwest China in summer” [Sci. Total Environ. 703 (2020) 134475] - Yue Zhao; Hong Ren; Junjun Deng; Linjie Li; Wei Hu; Lujie Ren; Siyao Yue; Yanbing Fan; Libin Wu; Jie Li; Yele Sun; Zifa Wang; et al. (Science of The Total Environment, 2026)

Retraction notice to “Cable-car measurements of vertical aerosol profiles impacted by mountain-valley breezes in Lushan Mountain, East China” [Sci. Total Environ. 768 (2021) 144198] - Jing Duan; Yong Chen; Wenling Wang; Jun Li; Xiaopeng Zhang; Guangxian Lu; Yunfei Che; Shujun Zhong; Shupo Ma; Peng Li; Junling An; Pingqing Fu (Science of The Total Environment, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Retraction notice to “Rapid transition of aerosol optical properties and water-soluble organic aerosols in cold season in Fenwei Plain” [Sci. Total Environ. 829 (2022) 154661] - Aodong Du; Yan Li; Jiaxing Sun; Zhiqiang Zhang; Bo You; Zhijie Li; Chun Chen; Jie Li; Yanmei Qiu; Xingang Liu; Dongsheng Ji; Wenjie Zhang; et al. (Science of The Total Environment, 2026)

Warm-season non-refractory PM2.5 composition in urban Tianjin and Beijing: Two megacities of the North China Plain - Qingqing Wang; Lu Lei; Yanpei Li; Wei Hu; Libin Wu; Junjun Deng; Jin Feng; Chun Chen; Borong Cheng; Jiang Zhu; Pingqing Fu; Yele Sun; et al. (Journal of Environmental Sciences, 2026)

Characteristics and source analysis of fluorescent aerosol particles at a typical rural site in the North China Plain during autumn and winter - Yang Zhou; Wei Hu; Siyao Yue; Wanyun Xu; Rui Jin; Boran Hua; Zihe Li; Libin Wu; Junjun Deng; Jiangchuan Tao; Nan Ma; Hang Su; et al. (Atmospheric Environment, 2026)

Microbial adaptation and environmental co-selection drive antimicrobial resistance risk in agricultural ditches, evidence from the multilevel ditch-river continuum - Xiangyao Wu; Yulin Qi; Lingchen Meng; Keyan Li; Chao Ma; Dietrich A. Volmer; Chunmei Chen; Peizhe Sun; Pingqing Fu; Zhifeng Yan (Journal of Hazardous Materials, 2026)

Direct measurement of aerosol acidity: recent advances, challenges, and opportunities - Mingjin Tang; Qishen Huang; Guangjie Zheng; Shiguo Jia; Shaojie Song; Guohua Zhang; Pingqing Fu; Tong Zhu (Science Bulletin, 2026)

High-resolution mass spectrometry reveals escalating concentrations of organophosphate esters in Yangtze River Basin soils along the upstream-to-downstream transect - Shuai Gong; Jianan Huang; Jianhua Li; Guanyong Su; Pingqing Fu (Environmental Pollution, 2026)

Interannual variability in marine isoprene emissions modulated by ENSO dynamics - Mengying Sun; Lei Song; Lehui Cui; Hao Liu; Yunting Xiao; Libin Wu; Wei Hu; Pingqing Fu; Jialei Zhu (Science China Earth Sciences, 2026)

Use of stable nitrogen isotopes in atmospheric aerosol research - Jingqi Bai; Libin Wu; Qingzi Zhao; Ke Xin; Wei Hu; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2026)

The preferential fractionation of dissolved organic matter (DOM) by co-precipitation with iron in diverse environmental conditions - Tingcang Hu; Chunmei Chen; Yulin Qi; Pingqing Fu; Si-Liang Li (Journal of Hydrology, 2026)

Characterization and influencing factors of hydroxymethanesulfonate (HMS) in the North China plain: integration of field measurements and theoretical calculations - Chun Chen; Haijie Zhang; Yele Sun; Junling Li; Zhiqiang Zhang; Jian Gao; Rui Gao; Lianfang Wei; Nan Ma; Wanyun Xu; Pingqing Fu (Atmospheric Environment, 2026)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Light absorption and molecular composition of brown carbon in Nanjing, China: Large contribution of biomass burning and secondary formation - Junjun Deng; Xinfeng Wang; Jialei Zhu; Wei Hu; Libin Wu; Pingqing Fu (Journal of Environmental Management, 2025)

Corrigendum to “ Atmospheric aging effects on aerosol ice nucleation” [Earth-Science Reviews, 269 (2025), 105176] - Ziye Huang; Wei Hu; Jie Chen; Jialei Zhu; Zhijun Wu; Yue Zhang; Pingqing Fu (Earth-Science Reviews, 2025)

Atmospheric aging effects on aerosol ice nucleation - Ziye Huang; Wei Hu; Jie Chen; Jialei Zhu; Zhijun Wu; Yue Zhang; Pingqing Fu (Earth-Science Reviews, 2025)

Sources and potential health indicators in urban aerosols revealed by gas chromatography-mass spectrometry combined with nitrogen chemiluminescence detector: evidence from a megacity (Tianjin) of China - Jingying Ma; Yulin Qi; Yufu Han; Jinfeng Ge; Ling Wen; Xiaoli Fu; Wei Hu; Zongbo Shi; Dietrich A. Volmer; Pingqing Fu (Atmospheric Environment, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Aqueous production of sulfur-containing aerosols from nitroaromatic compounds and SO2 in wintertime urban haze - Ning Yang; Junfeng Wang; Daniel J. Jacob; Jianhuai Ye; Ming Sheng; Mutong Niu; Yiming Qin; Xinlei Ge; Yele Sun; Zifa Wang; Yuhang Wang; Fengchang Wu; et al. (Science Bulletin, 2025)

Qualitatively elucidating the molecular characteristics of precursors for saturated halogenated disinfection byproducts in chlorinated urban eutrophic lake water by ultrahigh-resolution mass spectrometry - Shixi Wu; Qing-Long Fu; Manabu Fujii; Jibao Liu; Ahmed Elreedy; Xin Yang; Pingqing Fu; Yanxin Wang (Journal of Hazardous Materials, 2025)

Vertical distribution and seasonal variations of dicarboxylic acids in urban PM2.5: Insights from multi-level observations on 600 m Canton tower in Guangzhou - Dian Ye; Shengzhen Zhou; Yuxuan Liang; Chunlei Cheng; Chenglei Pei; Yao Li; Min Gao; Xijing Sun; Siqi Chen; Jian Hang; Pingqing Fu; Shaojia Fan (Atmospheric Environment, 2025)

Mass deposition of microbes from wildfire smoke to the sea surface microlayer - Siyao Yue; Yafang Cheng; Lishan Zheng; Senchao Lai; Shan Wang; Tianli Song; Linjie Li; Ping Li; Jialei Zhu; Meng Li; Lianfang Wei; Chaoqun Ma; et al. (Limnology and Oceanography, 2025)
Microbes in the sea surface microlayer (SML) are key to connecting the ocean and the atmosphere, affecting the exchange of matter, momentum, and heat at the interface. However, their sources have never been quantified systematically. Seawater has long been deemed their major source, whereas atmospheric deposition is regarded as trivial or merely providing additional nutrients. Here, combining atmospheric observations and quantitative budget analyses, we show that during the Indonesian peatland wildfire events the smoke can directly deposit abundant microbes into the SML, which can be comparable to the estimated supply from seawater and potentially diversify the microbial community of the SML. This land–air–ocean interaction is relevant for global climate, as it may induce previously unknown effects on the air–sea interactions, especially in an increasingly warming future with more intensifying wildfires.

Global Soil Methane Uptake Estimated by Scaling Up Local Measurements - Jiawei Jiang; Zhifeng Yan; Jinshi Jian; Shushi Peng; Hanqin Tian; Kendalynn A. Morris; Robert M. Ellam; Jesper Riis Christiansen; Huai Chen; Jianzhi Dong; Si‐Liang Li; Pingqing Fu; et al. (Global Change Biology, 2025)
Aerobic soils remove methane from the atmosphere, but global soil methane uptake (SMU) estimates remain highly uncertain due to challenges in scaling local data. We develop a data‐driven approach to refine this global estimate by incorporating local data of 79,800 flux measurements from 198 sites. This novel approach links the global SMU budget to local SMU fluxes by varying its parameters with soil properties. Our 2003–2018 global SMU estimate is ~39.0 Tg CH 4 year −1 —about 30% higher than existing bottom‐up estimates and consistent with top‐down assessments. Cold grasslands and deserts were found to contribute nearly 30% of the total SMU, while disturbed agricultural biomes have the lowest SMU. The projected future global SMU is shaped by temperature and atmospheric methane, though local SMU is primarily influenced by changes in soil moisture. This study emphasizes the potential of soils in climate regulation and highlights the need to focus on key biomes for a better understanding of the soil‐atmosphere methane feedback and optimizing methane management strategies.

Decreased stability of soil dissolved organic matter under disturbance of periodic flooding and drying in reservoir drawdown area - Shengman Zhang; Yuchun Wang; Ming Sheng; Xueping Chen; Ziyuan Zhang; Shanze Li; Yong Qin; Pingqing Fu; Fushun Wang (Science of The Total Environment, 2025)

Unravelling the complex influence of dissolved organic matter on microbial diversity in a salinized lake - Weiying Feng; Xuezheng Yu; Jiayue Gao; Jin Hur; Fang Yang; Zhuangzhuang Feng; Haiqing Liao; José Manuel Gonçalves; Isabel Maria Duarte; Pingqing Fu (Environmental Research, 2025)

Characterization of Organic Aerosols in the Ambient Air of Raipur, Central India: Distribution, Seasonal Variations, and Source Apportionment - Shobhana Ramteke; Bharat Lal Sahu; Khageshwar Singh Patel; Piyush Kant Pandey; Sema Yurdakul; Pablo Martín-Ramos; Hong Ren; Pingqing Fu (Aerosol Science and Engineering, 2025)

RETRACTED: Seasonal variation and size distribution of aromatic acids in urban aerosols in Beijing, China - Di Liu; Shaofeng Xu; Yunchao Lang; Shengjie Hou; Lianfang Wei; Xiaole Pan; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Science of The Total Environment, 2024)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Compositions and sources of fluorescent water-soluble and water-insoluble organic aerosols - Hao Ma; Dandan Liu; Junjun Deng; Jiaming Zhao; Qiang Zhang; Zhimin Zhang; Wei Hu; Libin Wu; Pingqing Fu (Science of The Total Environment, 2024)

Potential impacts of land use and land cover change (LUCC) and climate change on evapotranspiration and gross primary productivity in the Haihe River Basin, China - Shaobo Sun; Baozhang Chen; Jianwu Yan; Lukas Van Zwieten; Hailong Wang; Jianzhi Dong; Pingqing Fu; Zhaoliang Song (Journal of Cleaner Production, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Molecular composition and sources of free amino acids in atmospheric aerosols from Mt. Tai and a nearby city - Qingzi Zhao; Libin Wu; Xiaoli Fu; Wei Hu; Yajie Wang; Yuantao Wang; Ke Xin; Jingjing Meng; Siyao Yue; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2024)

Seasonal characterization of chemical and optical properties of water-soluble organic aerosol in Beijing - Bo You; Zhiqiang Zhang; Aodong Du; Yan Li; Jiaxing Sun; Zhijie Li; Chun Chen; Wei Zhou; Weiqi Xu; Lu Lei; Pingqing Fu; Shengjie Hou; et al. (Science of The Total Environment, 2024)

Variability in morphology of soot particles during non-cloud and in-cloud processes - Yuanyuan Wang; Liang Xu; Zexuan Zhang; Jian Zhang; Lei Liu; Yinxiao Zhang; Yuner Pang; Qi Yuan; Pingqing Fu; Dantong Liu; Weijun Li (Atmospheric Environment, 2024)

Characteristics of sub-micron aerosols above the urban canopy in Beijing during warm seasons - Qingqing Wang; Wei Du; Wei Zhou; Yingjie Zhang; Conghui Xie; Jian Zhao; Weiqi Xu; Guiqian Tang; Pingqing Fu; Zifa Wang; Yele Sun; Lin Peng (Science of The Total Environment, 2024)

Chemodiversity of organic nitrogen emissions from light-duty gasoline vehicles is governed by engine displacements and driving speed - Huixia Han; Hongxuan Du; Shuang Chen; Yisheng Xu; Lihong Ren; Yu Chen; Yeguang Cai; Kexin Wang; Xinping Yang; Mingliang Fu; Yan Ding; Pingqing Fu (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Modelling of sulfur chemistry in a fog episode in northern China and implication for the efficacy of SO2 emission control - Leyi Yuan; Mingxu Liu; Xinyi Dang; Hao Wu; Fang Shang; Lianfang Wei; Pingqing Fu; Yu Song; Min Hu (Atmospheric Environment, 2024)

Analysis of amino acid enantiomers in ambient aerosols: Effects and removal of coexistent aerosol matrix - Ying Li; Xiaoying Li; Libin Wu; Luhan Shi; Shan Wang; Pingqing Fu; Yingyi Zhang; Senchao Lai (Journal of Environmental Sciences, 2024)

Seasonal variation and dissolved organic matter influence on the distribution, transformation, and environmental risk of pharmaceuticals and personal care products in coastal zone: A case study of Tianjin, China - Wenrui Yao; Yulin Qi; Yufu Han; Jinfeng Ge; Yuanyuan Dong; Jianwen Wang; Yuanbi Yi; Dietrich A. Volmer; Si-Liang Li; Pingqing Fu (Water Research, 2024)

Hydroxy fatty acids in the surface Earth system - Wenxin Zhang; Wei Hu; Quanfei Zhu; Mutong Niu; Na An; Yuqi Feng; Kimitaka Kawamura; Pingqing Fu (Science of The Total Environment, 2024)

Source partitioning using phosphate oxygen isotopes and multiple models in a large catchment - Ziteng Wang; Liyan Tian; Changqiu Zhao; Chenjun Du; Jun Zhang; Fuhong Sun; Teklit Zerizghi Tekleab; Rongfei Wei; Pingqing Fu; Daren C. Gooddy; Qingjun Guo (Water Research, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

Direct evidence of pyrogenic aerosol iron by intrusions of continental polluted air into the Eastern China Seas - Liang Xu; Minkang Zhi; Xiaohuan Liu; Huiwang Gao; Xiaohong Yao; Qi Yuan; Pingqing Fu; Weijun Li (Atmospheric Research, 2023)

Organic aerosols in the inland Tibetan Plateau: New insights from molecular tracers - Xin Wan; Pingqing Fu; Shichang Kang; Kimitaka Kawamura; Guangming Wu; Quanlian Li; Shaopeng Gao; Zhiyuan Cong (Science of The Total Environment, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Sedimentary organic molecular compositions reveal the influence of glacier retreat on ecology on the Tibetan Plateau - Siwei Shi; Hai Xu; Yong Shui; Dandan Liu; Qiaorong Xie; Kang'en Zhou; Jin Zhang; Yunping Song; Jing Wang; Chukun Hu; Yuchun Wang; Pingqing Fu (Science of The Total Environment, 2023)

Fluorescence Properties and Chemical Composition of Fine Particles in the Background Atmosphere of North China - Ping Li; Siyao Yue; Xiaoyang Yang; Di Liu; Qiang Zhang; Wei Hu; Shengjie Hou; Wanyu Zhao; Hong Ren; Gang Li; Yuanguan Gao; Junjun Deng; et al. (Advances in Atmospheric Sciences, 2023)

Corrigendum to “Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China” [Sci. Total Environ. 857 (2023) 159337] - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Sedimentary organic matter molecular composition reveals the eutrophication of the past 500 years in Lake Daihai, Inner Mongolia - Chukun Hu; Hai Xu; Siwei Shi; Jianghu Lan; Kang'en Zhou; Jin Zhang; Yunping Song; Jing Wang; Pingqing Fu (Environmental Research, 2023)

Size distributions of molecular markers for biogenic secondary organic aerosol in urban Beijing - Di Liu; Shaofeng Xu; Yunchao Lang; Shengjie Hou; Lianfang Wei; Xiaole Pan; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Ice nucleation activity of airborne pollen: A short review of results from laboratory experiments - Peimin Duan; Wei Hu; Zhijun Wu; Kai Bi; Jialei Zhu; Pingqing Fu (Atmospheric Research, 2023)

Influence of aerosol physicochemical properties on CCN activation during the Asian winter monsoon at the summit of Mt. Lu, China - Jing Duan; Yong Chen; Xiaopeng Zhang; Wenling Wang; Shujun Zhong; Jun Li; Guangxian Lu; Chungang Fang; Lijun Guo; Pingqing Fu (Atmospheric Environment, 2023)

Size-Resolved Characteristics and Sources of Inorganic Ions, Carbonaceous Components and Dicarboxylic Acids, Benzoic Acid, Oxocarboxylic Acids and α-Dicarbonyls in Wintertime Aerosols from Tianjin, North China - Subba Rao Devineni; Chandra Mouli Pavuluri; Shuang Wang; Lujie Ren; Zhanjie Xu; Peisen Li; Pingqing Fu; Cong-Qiang Liu (Aerosol Science and Engineering, 2023)

Diurnal variations in primary and secondary organic aerosols in an eastern China coastal city: The impact of land-sea breezes - Qiang Zhang; Wei Hu; Hong Ren; Jianbo Yang; Junjun Deng; Dawei Wang; Yele Sun; Zifa Wang; Kimitaka Kawamura; Pingqing Fu (Environmental Pollution, 2023)

Accumulation of dissolved organic matter in the transition from fresh to aged seasonal snow in an industrial city in NE China - Zhen Mu; Xiaoying Niu; Christian George; Xinke Wang; Rujin Huang; Yuling Ma; Wei Pu; Yulin Qi; Pingqing Fu; Junjun Deng; Chao Ma; Nan Hu; et al. (Science of The Total Environment, 2023)

Chemistry of PM2.5 in haze events in two East Asian cities during winter–spring 2019 - Jayant Nirmalkar; Jinsang Jung; Sangbong Han; Zhichao Dong; Zhanjie Xu; Pingqing Fu; Chandra Mouli Pavulari (Atmospheric Environment, 2023)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

Biological Aerosol Particles in Polluted Regions - Wei Hu; Zihan Wang; Shu Huang; Lujie Ren; Siyao Yue; Ping Li; Qiaorong Xie; Wanyu Zhao; Lianfang Wei; Hong Ren; Libin Wu; Junjun Deng; et al. (Current Pollution Reports, 2020)

Impact of Arctic amplification on declining spring dust events in East Asia - Jun Liu; Dongyou Wu; Guangjing Liu; Rui Mao; Siyu Chen; Mingxia Ji; Pingqing Fu; Yele Sun; Xiaole Pan; Hongchun Jin; Yubin Zhou; Xin Wang (Climate Dynamics, 2020)
Dust aerosols play key roles in affecting regional and global climate through their direct, indirect, and semi-direct effects. Dust events have decreased rapidly since the 1980s in East Asia, particularly over northern China, primarily because of changes in meteorological parameters (e.g. surface wind speed and precipitation). In this study, we found that winter (December–January–February) Arctic amplification associated with weakened temperature gradients along with decreased zonal winds is primarily responsible for the large decline in following spring (March–April–May) dust event occurrences over northern China since the mid-1980s. A dust index was developed for northern China by combining the daily frequency of three types of dust event (dust storm, blowing dust, and floating dust). Using the empirical orthogonal function (EOF) analysis, the first pattern of dust events was obtained for spring dust index anomalies, which accounts for 56.2% of the variability during 1961–2014. Moreover, the enhanced Arctic amplification and stronger Northern Hemisphere annular mode (NAM) in winter can result in the anticyclonic anomalies over Siberia and Mongolia, while cyclonic anomalies over East Europe in spring. These results are significantly correlated with the weakened temperature gradients, increased precipitation and soil moisture, and decreased snow cover extent in the mid-latitude over Northern Hemisphere. Based on the future predictions obtained from the Fifth Climate Models Intercomparison Project (CMIP5), we found that the dust event occurrences may continually decrease over northern China due to the enhanced Arctic amplification in future climate.

Tissue-specific δ 13 C in ancient and modern tropical seabirds and flying fish in the Xisha Islands, South China Sea - Libin Wu; Liqiang Xu; Shengjie Hou; Xueying Wang; Pingqing Fu; Xiaodong Liu (Isotopes in Environmental and Health Studies, 2018)

High abundances of dicarboxylic acids, oxocarboxylic acids, and α-dicarbonyls in fine aerosols (PM2.5) in Chengdu, China during wintertime haze pollution - Xiao-dong Li; Zhou Yang; Pingqing Fu; Jing Yu; Yun-chao Lang; Di Liu; Kaori Ono; Kimitaka Kawamura (Environmental Science and Pollution Research, 2015)

Temporal and spatial distributions of dissolved organic carbon and nitrogen in two small lakes on the Southwestern China Plateau - Wen Li; Fengchang Wu; Congqiang Liu; Pingqing Fu; Jing Wang; Yi Mei; Liying Wang; Jianyang Guo (Limnology, 2008)